Essentials of Economics - Schiller, Bradley R. (McGraw-Hill, 2014)
The 9th edition is benefitted by SmartBook, the first adaptive reading experience designed to engage students with the content in an active and dynamic way, as opposed to the passive and linear reading experience they are used to. As a result, students are more likely to master and retain important concepts in the survey course.